Tradisi Fidaan Sebagai Simbol Dominasi Sosial Pada Masyarakat Undaan Kudus - Alfiyan Chasanul Muna; Jufri, Masudi; Farihah, Irzum (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2025)
Islamic teachings emphasize equality, piety, and social solidarity, values that are manifested in various Indonesian Muslim rituals, including the fidaan tradition. This study examines fidaan in Undaan Kudus not only as a spiritual ritual for the deceased but also as a social practice embedded with power relations and symbolic meanings. Using a qualitative descriptive-analytical approach, data were collected through in-depth interviews with religious leaders and community members. Drawing on Clifford Geertz’s symbolic interpretation and Anthony Giddens’ structuration theory, the study reveals that fidaan functions as a system of symbols that mediates between worldview and ethos while simultaneously reproducing social hierarchy through religious authority and material resources. Although perceived as voluntary and adaptable, fidaan implicitly reinforces stratification and symbolic recognition within the community. This research contributes to the understanding of local Islamic rituals as arenas where spirituality, social identity, and domination intersect in everyday religious life.